Increase in convective heat transfer over a backward-facing step immersed in a water-based tio2 nanofluid - Oon, Cheen Sean; Amiri, Ahmad; Chew, Bee Teng; Kazi, Salim Newaz; Shaw, Andy; Al-Shamma'a, Ahmed (Begell House, 2018)
Investigation of flow separation and reattachment of 0.2% water-based TiO2 nanofluid in an annular suddenly expanding pipe is presented in this paper. Such flows occur in various engineering and heat transfer applications. A computational fluid dynamics package (FLUENT) is used to study turbulent nanofluid flow in this research. Only a quarter of an annular pipe was investigated and simulated because of its symmetrical geometry. Standard k–ε second-order implicit, pressure based-solver equations are applied. Reynolds numbers between 17,050 and 44,545, step height ratio of 1.82, and a constant heat flux of 49,050 W/m2 were utilized in simulation. The numerical simulation results show that increase in the Reynolds number leads to an increase of the heat transfer coefficient and of the Nusselt number. Moreover, the surface temperature dropped to its lowest value after the expansion and then gradually increased along the pipe. Finally, the chaotic movement and high thermal conductivity of the TiO2 nanoparticles have contributed to the overall heat transfer enhancement of the nanofluid.